PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN JAMINAN ASET TERHADAP KEBIJAKAN DIVIDEN - Yurinawati, Widya; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of financial performance (profitability, liquidity, and debt), firm size and assets assurance to the dividend policy. In this research profitability has been measured by using Return on Assets (ROA)formula, liquidity has been measured by using Current Ratio (CR) formula, debt has been measured by using Debt to Equity Ratio(DER) formula, firm size has been measured by using Total Asset formula, assets assurancehas been measured by using (COL) formula, and dividend policy has been measured by using Dividend Payout Ratio (DPR) formula. The population is manufacturing companies which are listed in Indonesia Stock Exchange (IDX). The sample collection technique has been done by using purposive sampling and 12 companies have been as samplesand the criteria of manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2015 periods. The hypothesis test has been carried out by using multiple linear regressions analysis. The result of the research shows that profitability gives influence to the dividend policy which means that when the profitability ratio is high, the dividend which is shared to the investors will be large as well. Meanwhile, liquidity, debt, firm size, and assets assurance do not give any influence to the dividend policy which means that dividend policy cannot be influenced by liquidity, debt, firm size and assets assurance.Keywords: Financial Performance, Firm Size, Assets Assurance, Dividend Policy.